Adult executive functioning inventory (ADEXI): Validity, reliability, and relations to ADHD - Holst, Ylva (Int J Methods Psychiatr Res, 2017)
This study examined the psychometric properties of the Adult Executive Functioning Inventory (ADEXI). This new executive functioning (EF) rating instrument has the advantage of being brief (14 items) and focusing specifically on working memory and inhibitory control. Results showed that scores on the ADEXI had high internal consistency and adequate test–retest reliability, but low concurrence between self‐ratings and other ratings. High and statistically significant correlations were found between ADEXI scores and scores from another EF rating instrument, whereas the correlations between ADEXI scores and neuropsychological test scores were weak and often non‐significant. Furthermore, with regard to discriminant validity, individuals with attention deficit hyperactivity disorder (ADHD) had significantly higher scores on both the inhibition and working memory subscales compared to clinical as well as non‐clinical controls. The results showed high specificity, but relatively low sensitivity, when discriminating between adults with ADHD and non‐clinical controls. Conclusively, the ADEXI can be a valuable screening instrument for assessing deficits in working memory and inhibitory control. However, similarly to other EF ratings, the ADEXI should be used as a complement rather than as a replacement for neuropsychological tests, and the low interrater reliability suggests that ratings from multiple sources is preferable compared to relying solely on self‐ratings.